Personality features ina sample of psychophysiological insomnia patients - Luciane Bizari Coin de Carvalho; Eliane Aversa Lopes; Luciana Silva; Marilaine Medeiros de Almeida; Tatiana Almeida e Silva; Afonso Carlos Neves; Lucila Bizari Fernandes do Prado; Gilmar Fernandes do Prado (Arquivos de Neuro-Psiquiatria)
The personality is the way people express themselves inside the environment they live. Sleep, quality or quantity, is a way of this physical and psychological expression of well being. Psychological factors, associated with psychophysiological insomnia (PPI) suggest an exaggerated perception of the difficulties to fall asleep. Worries, anxiety and the fear of not sleeping produce a bad sleep quality or sleep misperception. This study aims to identify personality features associated with PPI throughout Rorschach test (RT). METHOD: We studied 32 patients with PPI (22 women), between 29 and 75 years old. We excluded patients with other sleeping or psychiatric disorders. We analysed the data from PPI patients submitted to the RT and we compared our results with the standard data. RESULTS: We noticed a significant increase in global answers and a significant decrease in detailed answers; a trend of a low number of answers; great number of shape and animal answers, especially for women. CONCLUSION: The features of the PPI patient's personality were daily problems insecure and the incapability to avoid or remove them from their thought, making bedtime a time for worries to appear again and motivate insomnia.